Adaptive estimation for affine stochastic delay differential equations - Markus Reiß (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2003)
Stochastic delay differential equations (SDDEs for short) appear naturally in the description of many processes, e.g. in population dynamics with a time lag due to an age-dependent birth rate (Scheutzow 1981), in economics where a certain "time to build" is needed (Kydland and Prescott 1982) or in laser technology (Garcia-Ojalvo and Roy 1996), in finance (Hobson and Rogers 1998) and in many engineering applications, see Kohmanovskii and Myshkis (1992) for an overview. They are also obtained as continuous-time limits of time series models, e.g. Jeantheau (2001), Reiß (2001). Among the huge variety of types of equations, the so-called affine stochastic delay differential equations form the fundamental class. They generalize the Langevin equation leading to the Ornstein-Uhlenbeck process and appear as continuous-time limits of linear autoregressive schemes.
urn:nbn:de:kobv:11-10050055
Keywords: 330; Analysis; Stochastischer Prozess; Schätztheorie; Theorie